Impact of Accountable Care Organizations on Prostate Cancer Screening and Biopsies in the United States. Issue 3 (May 2019) - Trinh, Quoc-Dien; Sun, Maxine; Krasnova, Anna; Ramaswamy, Ashwin; Cole, Alexander P.; Fletcher, Sean A.; Friedlander, David F.; Sammon, Jesse D.; Lipsitz, Stuart R.; Kibel, Adam S.; Weissman, Joel S.
Abstract: Introduction: Accountable care organizations are designed to financially incentivize efficiency and reduce low value care. To determine if accountable care organizations have impacted prostate cancer screening patterns, we analyzed trends in prostate specific antigen screening and prostate biopsies by accountable care organization and nonaccountable care organization providers. Methods: Using a random 20% sample of Medicare claims, we selected men 66 years old or older. In 2014 beneficiaries were attributed to accountable care organization and nonaccountable care organization providers using a modified Medicare Shared Savings Program algorithm. Beneficiaries treated by these same providers in 2010 served as the control population. Inverse probability weighting and difference in differences analyses were used to compare trends in prostate specific antigen screening and prostate biopsies in 2010 and 2014. Analyses were stratified by the age groups 66 to 69 years old and 70 years old or older. Results: Among the beneficiaries treated by accountable care organization and nonaccountable care organization providers, prostate specific antigen screening rates were 62.4% and 60.5% in 2010 vs 55.9% and 54.4% in 2014 in men 66 to 69 years old, respectively (p=0.3). Prostate biopsy rates were 2.5% and 2.3% in 2010 vs 1.7% and 1.6% in 2014, respectively (p=0.6). In men 70 years old or older, prostate specific antigen screening rates were 54.3% and 54.2% in 2010 vs 46.0% and 46.4% in 2014, respectively (p=0.2). Similarly, prostate biopsy rates were 1.8% and 1.7% in 2010 vs 1.1% and 1.1% in 2014, respectively (p=0.7). Conclusions: Although decreasing the use of low value services is a fundamental goal of accountable care organizations, prostate specific antigen screening and prostate biopsy trends were similar for accountable care organization and nonaccountable care organization providers across all age groups in the study years. This finding suggests that accountable care organization implementation did not have an impact on prostate specific antigen screening or prostate biopsy use.